2014
DOI: 10.1155/2014/413592
|View full text |Cite
|
Sign up to set email alerts
|

Propeller Excitation of Longitudinal Vibration Characteristics of Marine Propulsion Shafting System

Abstract: The submarine experiences longitudinal vibration in the propulsion shafting system throughout most of run. A transfer matrix model of the propulsion shafting system, in which the dynamic characteristics of oil film within thrust bearing are considered, is established to describe the dynamic behavior. Using hydrodynamic lubrication theory and small perturbation method, the axial stiffness and damping of oil film are deduced in great detail, followed by numerical estimation of the foundation stiffness with finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Finally, concluded that longitudinal dynamics were not discussed in API standards. The longitudinal vibrations in a marine propulsion system has been studied by Zhang et al [22] using transfer matrix method. Hydrodynamic lubrication theory and small perturbation method were used to determine the axial stiffness and damping of oil film.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, concluded that longitudinal dynamics were not discussed in API standards. The longitudinal vibrations in a marine propulsion system has been studied by Zhang et al [22] using transfer matrix method. Hydrodynamic lubrication theory and small perturbation method were used to determine the axial stiffness and damping of oil film.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [7][8][9][10] and others have carried out relevant theoretical research on the longitudinal vibration of shafting and also pointed out that the longitudinal stiffness parameters of propulsion shafting are the main parameters affecting the longitudinal vibration of shafting. A kind of propulsion shafting with hydraulic vibration reduction is presented, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…[4] by modelling of the propeller shaft crankshaft with piston under the influence of angular and axial forces acting on the propeller was investigated. Between propeller and 1 st order crankshaft journal, 5 th and 6 th order piston-crank journal's shaft torsional vibrations have been observed frequency change.…”
Section: Introductionmentioning
confidence: 99%